Evaluation of hydro-chemical facies and surface water quality dynamics using multivariate statistical approaches in Southern Nigeria - E. A Ubuoh; F. U Nwogu; E. Q Ossai-Abeh; J. C Ikwuemesi; A. O Oke; J. D Umoh (Scientific Reports)
Abstract The geochemical and chemical constituents of river water quality could be influenced by human activities and organic processes like water interacting with the lithogenic structure that the river flows through. Evaluating evidence based primary root of the predominant pollutant ions, their interactions as well as the factors controlling their dominance is crucial in studies regarding water environment and hydrology especially as most studies focus on theoretical methods. In order to understand the water cycle, safeguard surface water resources, and preserve the human environment, this study evaluated surface water hydro-chemical facies, quality dynamics, and portability in southern Nigeria using multivariate statistical approaches by analyzing selected hydro-chemical characteristics as indicators of pollution along the river during wet and dry seasons. Twenty water samples were taken, analyzed, and subjected to mathematical statistics: Gibbs plot, trilinear piper analysis, stiff pattern analysis, ionic scatter analysis, correlation, and principal component analysis. Result of surface water recorded mean pH ranges from 4.8 for wet season and 5.3 for dry season, above the WHO, and during dry season TDS, Mg2+, Pb, and Cd were above the WHO limits, respectively. Abundance of cation and anion in surface water was in a decreasing trend of: HCO3 > Ca2+ > Mg2+ > Cl− > Na+ > SO4 2− > K + > NO3 −. Trilinear plot, stiff pattern, and Gibbs ratio indicated hydrochemical facie of water dominated by calcium bicarbonate (Ca-HCO3) water type. From plots and ionic ratio, the major hydrochemical process of water chemistry during wet and dry seasons was rock-water interaction arising majorly from weathering processes. Ionic ratios of Ca2+ and Mg2+ 1, Ca2+ and HCO2− [1:2], Ca2+ + Mg2+ and HCO3− + SO42− [1:1], revealed dissolution of dolomite as their common origin, with total cations in wet and dry seasons ranging between 43 and 57% and total anions: 37.3–62.7, with dry season dominance. The overall WQI of the river seemed good quality due to rapid flow and self-purification of the river but may be harmful in the future. It was recommended that constant surveillance and monitoring of human activities along waterways be enforced in order to ensure that undesirable pollution levels don’t occur in the river.